Detection And Monitoring of E-Waste Associated Dumping Locations in Landfill in Patna Using Multi-Temporal Satellite Spectral Images - Daya Shankar Singh, (International Journal of Scientific Research in Science and Technology, 2024)
Remote sensing has been proved an important tool for detection and monitoring of landfills and their expansion over time. Remote sensing can provide rapid synoptic view of the dynamic events and activity imposed by any agency on earth’s environment. Availability of a variety of high resolution multispectral sensors, it can provide accurate information, making it anappropriate technology for multiple applications. The prime task ofpresent investigation is to innovate a technique based on remote sensing for landfill identification and monitoring. The presence of E-waste in solid waste has been detected using multi-spectral images at the Bairialandfill site in Patna. The digital recording of solid waste disposal at village Bairiahas been made possible by satellite spectral images. The Bairia landfill site started in 2010. Polymer, metal and household waste have been found in abundance in satellite images at this site. By the year 2024, the landfilled has spread over 66 acres constituting several layers and heaps of waste in marked areas. Growth of algae on the old garbage dump is proof of water retention in solid waste.Many metal contaminants are found in water, flowing as seepage, which increases contamination of groundwater and surrounding surface water.Growth of red coloured algae on the water inundation around the identified landfill site proves that the water contains various contaminated elements like heavy metals.
Keywords: Remote Sensing; Solid Waste; Metals; Spectral Indices; Polymers